Numerical investigation of angle parameters of tip sails for improvement of aircraft flight performance - Minghao Yang; Shu Li; Xiao Bian; Jiayang Liu (Engineering Applications of Computational Fluid Mechanics)
Inspired by the tip feathers of soaring birds, the device of tip sails was designed and installed on the wing to achieve drag reduction. The influences of design parameters including cant angles, toe angles and twist angles on aerodynamic characteristics of tip sails were investigated through 77 cases of 11 configurations at 7 different angles of attack. According to the results grouped, the optimal cant angles [Formula: see text] were determined. By adjusting the toe angles, drag reduction can be improved under different flight conditions. The decreasing twist angles can inhibit flow separation on sail surface. The optimal toe angles [Formula: see text] and twist angles [Formula: see text] resulted in the weakest flow separation. Ensuring that the twist angle of each sail is [Formula: see text] less than that of the corresponding toe angle can effectively inhibit flow separation on the sail surface. The tip sails can also split and weaken the wingtip vortex. In addition, in the validation of the numerical method, we also investigate the influence of numerical schemes and turbulence models on the results of wingtip vortex flow. In the cases with unstructured meshes, the third-order finite volume scheme had higher computational efficiency than the traditional second-order finite volume scheme in obtaining grid independent solutions, and the turbulence model with rotation correction can improve the calculation accuracy of the wingtip vortex flow. The results of this paper provide a valuable reference for the design of tip sails.